Multiscale Currents Observed by MMS in the Flow Braking Region. Issue 2 (20th February 2018) - Nakamura, Rumi; Varsani, Ali; Genestreti, Kevin J.; Le Contel, Olivier; Nakamura, Takuma; Baumjohann, Wolfgang; Nagai, Tsugunobu; Artemyev, Anton; Birn, Joachim; Sergeev, Victor A.; Apatenkov, Sergey; Ergun, Robert E.; et al.
Abstract: We present characteristics of current layers in the off‐equatorial near‐Earth plasma sheet boundary observed with high time‐resolution measurements from the Magnetospheric Multiscale mission during an intense substorm associated with multiple dipolarizations. The four Magnetospheric Multiscale spacecraft, separated by distances of about 50 km, were located in the southern hemisphere in the dusk portion of a substorm current wedge. They observed fast flow disturbances (up to about 500 km/s), most intense in the dawn‐dusk direction. Field‐aligned currents were observed initially within the expanding plasma sheet, where the flow and field disturbances showed the distinct pattern expected in the braking region of localized flows. Subsequently, intense thin field‐aligned current layers were detected at the inner boundary of equatorward moving flux tubes together with Earthward streaming hot ions. Intense Hall current layers were found adjacent to the field‐aligned currents. In particular, we found a Hall current structure in the vicinity of the Earthward streaming ion jet that consisted of mixed ion components, that is, hot unmagnetized ions, cold E × B drifting ions, and magnetized electrons. Our observations show that both the near‐Earth plasma jet diversion and the thin Hall current layers formed around the reconnection jet boundary are the sites where diversion of the perpendicular currents take place that contribute to the observed field‐aligned current pattern as predicted by simulations of reconnection jets. Hence, multiscale structure of flow braking is preserved in the field‐aligned currents in the off‐equatorial plasma sheet and is also translated to ionosphere to become a part of the substorm field‐aligned current system. Key Points: Multiscale field‐aligned currents in the boundary of the expanding plasma sheet during plasma jet braking intervals are resolved Intense Hall current layers are found at the inner boundary of the hot Earthward streaming ion jets and flow shear regions Both plasma jet diversion and Hall effects from reconnection region contribute to the structure of the substorm wedge currents